Mechanical Properties and Stress Analysis of Natural Fiber Reinforced Polymer Composite Spur Gear - M. Jayaraj; S. K. Ashok; Rama Thirumurugan; Dharmalingam Shanmugam; M. Mahendran (Журнал інженерних наук)
This research study investigates the mechanical properties of polymer composites reinforced with natural fibers, specifically Palmyra palm leaf stalk fiber (PPLSF) and Palmyra palm primary leaf stalk fiber (PPFLSF). Tensile, flexural, and impact strength were among the composites’ mechanical parameters generated by integrating these fibers into a polymer matrix and assessing them experimentally. Additionally, stress analysis of a spur gear was conducted using the finite element analysis software ABAQUS. The composite material properties obtained from the experimental investigation were used in the analysis to evaluate the gear’s stress distribution and deformation behavior. The bending stress at the pitch point of the natural composite gears for PPLSF, PPFLSF, and nylon synthetic material is analyzed using analytical and experimental methods by ABAQUS software. Finally, the results are compared with each other. The results show that stress induced by nylon is comparatively higher than that of PPLSF and PPFLSF fiber. By analyzing these composites’ strength, durability, and stress distribution under operating environments, the study aims to determine whether they are suitable substitutes for conventional materials.